The Effect of Ethnoscience Approach Through Problem Based Learning Model on Chemical Literacy Ability of Class XI Students on Reaction Rate Material at SMA Negeri 7 Gorontalo - Riryn Tahir; Hendri Iyabu; Julhim S. Tangio; Mangara Sihaloho; Wiwin Rewini Kunusa; Thayban Thayban (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The research aims to determine the effect of the ethnoscience approach through the problem-based learning model on the chemical literacy skills of Grade XI students in the reaction rate material at SMA Negeri 7 Gorontalo. The research employs a quasi experimental method with a nonequivalent control group design. The sample consisted of Grade XI IPA ( Natural Science) students from SMA Negeri 7 Gorontalo. The instrument used in this research was an essay test. Data processing and analysis were conducted using Microsoft Office Excel and SPSS version 16. The hypothesis test results on students’ post-test data using the Mann-Whitney test at a significance level of α = 0.05 showed that the Asymp. Sig. (2-tailed) value was less than 0.05 (0,002 < 0,05). Therefore, H1 was confirmed, and H0 was rejected. The N- Gain test results also indicated that the ethnoscience approach through the problem-based learning model was moderately effective in improving students’ chemical literacy skills in reaction rate material, with the experimental class achieving an N-Gain score percentage of 57.13% (moderately effective category), while the control class achieved a percentage of 31.42% (ineffective category). In conclusion, the ethnoscience approach through the problem-based learning model significantly affects students’ chemical literacy skills in reaction rate material.